ICT-supported Language Learning Tools for Chinese as a Foreign Language: a content review - Čok, Tina (Revija za elementarno izobraževanje, 2016)
The paper presents a meta-analysis of 37 scientific papers dealing with the use and adoption of ICT for learning and teaching Chinese as a foreign language. It has shown that systematic content reviews providing overall insight into the nature and level of development in the field are rare. The author tries to fill this content gap by answering three research questions: 1) What is the overall state of research in the field of ICT-assisted learning of CFL in terms of language teaching methods? 2) Which learning technologies are in use for the specific teaching and learning methods for Chinese as a foreign language? 3) Are some learning technologies used more often for practis ng specific language skills than others?